On-slide detection of enzymatic activities in selected single cells. Issue 36 (5th September 2017) - Keller, Josephine Geertsen; Tesauro, Cinzia; Coletta, Andrea; Graversen, Astrid Damgaard; Ho, Yi-Ping; Kristensen, Peter; Stougaard, Magnus; Knudsen, Birgitta Ruth
Abstract : Detection of human topoisomerase I activity in single cells using an on-slide array setup. Abstract : With increasing recognition of the importance in addressing cell-to-cell heterogeneity for the understanding of complex biological systems, there is a growing need for assays capable of single cell analyses. In the current study, we describe the measurement of human topoisomerase I activity in single CD44 positive Caco2 cells specifically captured from a mixed population on glass slides, which were dual functionalized with anti-CD44-antibodies and specific DNA primers. On-slide lysis of captured CD44 positive cells, resulted in the release of human topoisomerase I, allowing the enzyme to circularize a specific linear DNA substrate added to the slides. The generated circles hybridized to the anchored DNA primers and acted as templates for a solid support rolling circle amplification reaction leading to the generation of long tandem repeat products that were detected at the single molecule level in a fluorescent microscope upon hybridization of fluorescent labelled probes. The on-slide detection system was demonstrated to be directly quantitative and specific towards CD44 positive cells. Moreover, it allowed reproducible detection of human topoisomerase I activity in single cells.